Hackers Beware - Cole, Eric (Sams, 2001)
Hackers Beware starts with a roadmap of the various areas of hacking but quickly delves into the details of how specific attacks work and how to protect against them. Since most attacks we hear about either occur or are perceived to come from hackers, people are very interested "in how they do that"--The techniques hackers use to break into systems. Hackers Beware is unique in that it gives specific exploits, exactly how they work and how to protect against them. This book will help readers understand what security threats they are up against and what they need to do to protect against them. Some books cover this from a high level but do not get into the details of specific exploits and cover it in a case by case fashion. This book will cover the complete picture. It will not only describe how an exploit works but present the signature of the attack, what to look for on a network and how to protect against it.
Keywords: Computer security; Hackers; Sécurité informatique; Pirates informatiques